2021
DOI: 10.18488/journal.1.2021.117.345.354
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis towards the Sustainability and Management of Waqf’s Properties in Malaysia with References to Johor

Abstract: In Malaysia, waqf properties are held and put under the Department of Waqf, Zakat and Hajj (JAWHAR) at the federal level and under the State's Islamic Religious Council (SIRC) of respective states for the state level. However, all these properties need a lot of funds to manage them, and issues arose on sustainability and management of these waqf properties. The research found no guidelines identified explicitly in any investigation or findings on the appropriate guideline to solve this issue. Therefore, this r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…As a result, the mutawalli has considerable responsibility for ensuring that the waqf property is developed per the designation agreed upon and ratified by the donor (Yusoff et al. , 2021a, 2021b).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, the mutawalli has considerable responsibility for ensuring that the waqf property is developed per the designation agreed upon and ratified by the donor (Yusoff et al. , 2021a, 2021b).…”
Section: Resultsmentioning
confidence: 99%
“…Insufficient funds, lack of proper planning by the mutawalli waqf, waqf lands that are not registered under the State Islamic Religious Council (SIRC) and outdated data are some of the problems hindering the development of waqf. As a result, the mutawalli has considerable responsibility for ensuring that the waqf property is developed per the designation agreed upon and ratified by the donor (Yusoff et al, 2021a(Yusoff et al, , 2021b.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yusoff et al's article (2021) explored the drivers of female participation in male-dominated esports and their subsequent transition to the professional scene. In their interview with six female pro-gamers, the authors found that support and encouragement from primary (parents) and secondary (coworkers, the media, coaches, and opponents) socialization agents are increasing and prompting more female gamers to pursue gaming as a career.…”
Section: Resultsmentioning
confidence: 99%
“…Nearly a third of all esports income is generated in China—plausibly explaining why the Asian pro-gaming scene has been dissected from multiple angles (see Supplementary material, Appendix D for region-wise article distribution). While young males make up the bulk of esports followers, the number of female esports fans has climbed to 34% (Newzoo, 2022), and women are keen on making a career out of it (Yusoff et al, 2021). Concerns, however, remain as elite gamers are still men and female gamers have to work doubly hard to merit the same status as them (Kari & Karhulahti, 2016; Zeolides, 2015).…”
Section: Discussionmentioning
confidence: 99%